The incidence of surgical site dehiscence following full‐thickness gastrointestinal biopsy in dogs and cats and associated risk factors. (1st August 2017) - Swinbourne, F.; Jeffery, N.; Tivers, M.S.; Artingstall, R.; Bird, F.; Charlesworth, T.; Doran, I.; Freeman, A.; Hall, J.; Hattersley, R.; Henken, J.; Hughes, J.; et al.
Abstract : Objectives: The objectives of this study were to: (1) document the incidence of surgical site dehiscence after full‐thickness gastrointestinal biopsy in dogs and cats and (2) identify potential risk factors. Methods: Data relating to dogs and cats undergoing full‐thickness gastrointestinal biopsy were reviewed retrospectively following submission of a completed questionnaire by 12 referral institutions. Outcome measures were definite dehiscence, possible dehiscence (clinical records suggestive of dehiscence but not confirmed), suspected dehiscence (definite and possible combined) and death within 14 days. Logistic regression was planned for analysis of association of dehiscence with low preoperative serum albumin, biopsy through neoplastic tissue, biopsy alongside another major abdominal surgical procedure and biopsy of the colon. Results: Of 172 cats, two (1·2%) had definite dehiscence, and four (2·3%) had possible dehiscence. Low preoperative serum albumin was significantly associated with definite dehiscence in univariable analysis and with suspected dehiscence and death within 14 days in univariable analysis, but all odds ratios had wide 95% confidence intervals. A histopathological diagnosis of neoplasia was significantly associated with death within 14 days in univariable analysis. Of 195 dogs, two (1·0%) had definite dehiscence, and three (1·5%) had possible dehiscence. In dogs, there was no association between any outcome measure and the putative risk factors. Clinical Significance: Incidence of dehiscence following full‐thickness gastrointestinal biopsy was low in this study. When determining the appropriateness of biopsy in individual cases, this information should be balanced against the potentially life‐threatening consequences of dehiscence.